Analysis Of Maternal Hygiene Practices And Sanitation Knowledge On Stunting Incidence In Children Under Five At Sepatan Health Center, Tangerang Regency - Muhamarudin; Anindya, Pramita; Budipramana , Vicky Sumarki; Dagradi, Eric Mayo (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Stunting remains a significant global health challenge, profoundly impacting child growth and development, defined by a height-for-age z-score below -2 standard deviations of the WHO growth standards. Substandard sanitation and poor hygiene practices substantially elevate the risk of stunting, potentially by up to five-fold. Parental involvement, especially maternal knowledge and understanding of stunting, is crucial for its prevention. This study aimed to analyze the association between maternal hygiene practices, maternal sanitation knowledge, and stunting prevalence in toddlers. We conducted a cross-sectional, observational analytic study among mothers of stunted children aged 0-5 years within the working area of Puskesmas Sepatan, Tangerang Regency, Indonesia. A total of 63 respondents completed questionnaires assessing their hygiene behaviors and sanitation knowledge. Our findings indicate that most stunted toddlers had mothers with suboptimal hygiene practices, despite their sanitation knowledge generally being in the 'good' category. Spearman's correlation analysis revealed a significant association between maternal hygiene practices and stunting incidence (p=0.044), as well as between maternal sanitation knowledge and stunting incidence (p=0.000). This study concludes that both maternal hygiene practices and sanitation knowledge are significantly associated with stunting among toddlers in this Indonesian community, underscoring the critical need for targeted interventions focusing on behavioral change alongside educational initiatives to combat this pervasive public health issue.